Penapisan Inhibitor Protease yang Dihasilkan oleh Sponge Asal Kepulaun Seribu - Tati Nurhayati; Pipih Suptijah; Maggy T. Suhartono; Irman Febrian (Jurnal Pengolahan Hasil Perikanan Indonesia, 2004)
Several medicines showing protrease inhibitor mechanism are widely available in the markets. Among marine organisms, sponge is the big producer of bioactive compound, include protease inhibitor. The purpose of this research was to screen of protease inhibitor produced by sponge. Screening was be conducted using agar diffusion methods on ten of sponge which the extracted with methanol and distilled water. As test bacteria were used three species of pathogenic bacteria that is Escherichia coli, Pseudomonas aeruginosa, and Staphyloccocus aureus. The result of research showing that sponge which be extracted using methanol have low protease inhibitory activity (≤ 30%), while that which be extracted using distilled water have high protease inhibitory, that is extract of Jaspis stellifera and extract of Plakortis nigra (≥ 50%). The extract of Jaspis stellifera was inhibited of protease from Escherichia coli and Staphyloccocus aureus by minimum inhibitory concentration (MIC) 0.08%, while that extract of Plakortis nigra was inhibited protease from S. aureus by MIC 0.12%. Ethymenediamine tetraacetic acid (EDTA) was inhibited S. aureus and E. coli by MIC 0.16%. Based on the data, can be concluded that both the extract of sponge were potential as protease inhibitor.Keywords: Bacteria, protease inhibitor, screening, sponge